Navigating the intersection of mental health and kidney health: a systematic review of antidepressant safety in renal impairment - Hooria Sarwar; Muhammad Zeshan; Najeeb Hussain; Esha Mogali; Rehan Durrani; Iana Malasevskaia (Discover Mental Health)
Abstract Depression is a prevalent mental health condition that significantly impacts adults with impaired renal function, yet the safety and efficacy of antidepressants in this population remain inadequately explored. Understanding how renal impairment affects antidepressant pharmacokinetics and clinical outcomes is essential for optimizing treatment strategies. This systematic review adhered to PRISMA 2020 guidelines, conducting a comprehensive literature search across multiple databases, including PubMed, ScienceDirect, ClinicalTrial.gov, and Medline. Studies were included if they evaluated the use of antidepressants in adults with renal impairment, assessing both safety and efficacy outcomes. The review identified 11 studies that met the inclusion criteria, with sample sizes ranging from 30 to 101,409 participants, yielding a total sample size of 192,684. The quality assessment of the included studies was conducted based on the type of study design, focusing on methodological rigor and relevance to the research question. While certain antidepressants demonstrate efficacy, their pharmacokinetic profiles necessitate careful monitoring and dose adjustments in patients with different levels of renal impairment. These insights underscore the need for individualized treatment approaches and highlight areas for future research to enhance care for this vulnerable population.